Analysis the Effect of Promotion Mix Strategy to Increase Sales on Consignment System Toward Food and Beverage - Laraswati, Dian Mutiah; Dellyana, Dina (Journal of Innovation, Business and Entrepreneurship, 2016)
Abstract.Development of food and beverage industry in Indonesia can be seen clearly. Therefore, the development of food and beverage industry in Indonesia has an impact to the growth of new food and beverage business or we can call the food and beverage start-up business. Based on author’s observation, generally start-up business will choose the form of selling that suitable to the budget and capital. For instance, selling on consignment system. However, consignment system has weakness, the weakness is low and long return toward sales in consignment system. One of food and beverage start-up business who has experienced that consignment system has a weakness in sales aspect is Strew it Doughnut Company. The expertise found that promotion has a leverage to the food products purchase, due to faster consumption rates. According to statement above, food and beverage start-up businesses which use consignment as their form of selling should take into consideration about promotion as one of strategy to increasing sales. In this research, the author will analyze the effect of promotion mix strategy to increase sales on consignment system toward food and beverage start-up. The author uses qualitative design to conduct this research. First step is to define the variable of promotion mix through literature review. The second step is to conduct the interview about the promotion mix method with three food and beverage start-up companies which use consignment as their form of selling, there are Futuristea, Puro and Du’crème. Next step is to analyze how each method of promotion mix give an impact to increasing sales in consignment system. The methods of promotion mix consist of advertising, sales promotion, public relation and personal selling. Those methods give diverse effects for their business in consignment system. The final result are sales promotion gives high impact to increasing sales. The second result is advertising and public relation, which give good contribution to increasing sales. Advertising and public relation gives moderate impact to increasing sales and the last is personal selling which has no impact to increasing sales. Keywords: promotion mix, consignment, sales